PARENTING PATTERN, SOCIOECONOMIC STATUS AND PARENT’S COMMUNICATION ON EARLY CHILDHOOD LANGUAGE ABILITY - Baiti, Noor; Metroyadi, Metroyadi; Wahyu, Wahyu (Journal of K6, Education and Management, 2019)
This study aims to describe the relationship parenting pattern and socioeconomic status through parent?scommunication on children's language ability in Kindergarten of Anjir Muara District. This study uses descriptive quantitative methods. The population were 300 children and sample were 173 people using the proportionate random sampling technique. Data colection uses quesioners and observation. Hypothesis testing uses Path Analysis. The results (1) there is significant relationship between parenting pattern and parent communication (2) there is significant relationship between the socioeconomic status and parent communication (3) there is significant relationship between parents parenting pattern and children's language ability (4) there is significant relationship between family socioeconomic status and children's language ability (5) there is significant relationship between parent communication and children's language ability (6) there is significant indirect relationship parenting pattern, parent?s communication on children's language ability (7) there is significant indirect relationship between socioeconomic status through parental communication on children's language ability.